17. EVALUATION OF OUTCOMES OF TOTAL HIP ARTHROPLASTY WITH MODIFIED LATERAL APPROACH AT SAIGON ITO HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the outcomes of total hip arthroplasty in 360 patients using a modified lateral approach at Saigon ITO Hospital over a 10-year period.Research objects and methods: This study included 360 cases, comprising 200 males and 160 females, aged 39-76 years, diagnosed with femoral neck fractures or hip joint necrosis, who underwent total hip arthroplasty using a modified lateral approach at Saigon ITO Hospital between 2014 and 2024.Results: The surgical time ranged from 60-90 minutes, with blood loss ranging from 200-300 ml. Hip joint function was assessed using the Harris Hip Score, with 84.4% achieving good to excellent results, 15.6% achieving fair results, and no poor results. Twelve cases (3.33%) experienced partial gluteus medius atrophy but without limitation in hip abduction function. There were two cases of infection and two cases of thromboembolism (0.55%). Postoperative wound bleeding occurred in five cases (1.38%), and one case (0.27%) of periprosthetic fracture was observed. Notably, there were no cases of postoperative hip dislocation.Conclusion: Total hip arthroplasty using a modified lateral approach is easy to perform, causes minimal soft tissue damage, yields good functional recovery of the hip joint, limits complications, and overcomes some existing drawbacks of the anterior and posterior approaches.
Keywords: Femoral neck fracture; femoral head necrosis; total hip arthroplasty with modified lateral approach.